PAT study on stress-field pinning in high-Tc superconductors - 李阳 王耘波 唐春光 马庆珠 曹国辉 魏龙 王文华 张天保 (Science China. Mathematics, 1997)
The simultaneous measurements of Doppler-broadened radiation spectra and lifetime spectra were performed by positron annihilation analysis on Eu-doped Y-123 superconductors.When the doping concentration reaches 30 % and 70 %,the density of defeat and its stress-field reach the maximum for (Y1-xEux) Ba2Cu3O7-y The pinning mechanism of such superconductors is discussed,and the results support the stress pinning mechanism.